Design, Fabrication and Testing of River Water Pump for Rural Communities - Khanal, Paras; Acharya, Shyamhari; Shrestha, Milan; Chitrakar, Sailesh; Neopane, Hari Prasad (Kathmandu University Journal of Science, Engineering and Technology, 2021)
This paper presents development of river water pump that can operate without fuel and electricity mostly applicable in rural communities that are close to a water stream. The river water pump consists of a propeller, drum, hose, rotary coupling and helical coil. The pump is driven by a propeller which is rotated by moving water. Because these pumps do not require any external energy or fuel, the operating cost for irrigation, as well as for other household purposes can be minimized. In this study, two different shaped pumps were fabricated and tested. Although the general mathematical relations for the design of the pump was kept constant for the two pumps, the variation of the shape of the drum was incorporated for comparing the performances. The main purpose of this study was to compare performance of the cylindrical shaped and conical shaped pump. It was found from this study that by making a conical shape of the drum, the total discharge could be maximized. However, the design of the supporting structure to withhold the pump on the river needs to be modified to balance the unsymmetrical distribution of the mass caused due to the conical shape. Compared to the conventional coil pump, this study also uses double layer of coil to enhance the overall performance of the pump. Thus, this study is expected to support in the product development within this family of the pump.